Patient self-screening stations for atrial fibrillation in general practice waiting rooms: process evaluation. (14th October 2021) - McKenzie, K; Lowres, N; Freedman, B; Orchard, J; Hespe, C; Giskes, K
Abstract: Background: Our previous work has identified factors relevant to general practitioner (GP)-led screening for atrial fibrillation (AF) in Australian general practices, with GPs indicating significant time constraints. AF SELF SMART (Atrial fibrillation self-screening, management and guideline recommended therapy) allows for opportunistic patient self-screening using purpose-built screening stations located in GP waiting rooms (figure 1). It utilises a single-lead ECG, with results automatically imported into the patient medical record for review during the GP consultation. AF SELF SMART may increase screening rates, but acceptability by practice staff is unknown. Purpose: Determine staff perspectives on opportunistic self-screening in practice waiting rooms, utilising AF SELF SMART. Method: 14 semi-structured interviews have been conducted with practice staff (GPs, receptionists and practice managers) across 3 practices participating in the AF SELF SMART pilot, with thematic analysis of results. Results: Several themes were identified. All staff acknowledged the importance of increasing screening for AF in the practice. GPs in particular placed a high value on AF screening for stroke prevention. GPs valued the increased information and accuracy provided by AF SELF SMART, as previously they checked patients for AF using manual methods, either routinely or as clinically indicated. There were differential impacts on workflow. GPs reported some small increase in workload but these were seen as being acceptable given the benefits of the program. Receptionists and Practice Managers reported significant interruptions to normal workflow associated with assisting patients. Receptionists routinely offered patients help with screening instead of patients screening independently. Staff perceived that patients were either unable to negotiate the self-screening process by themselves, or did not want to try. Given the increase in workload associated with assisting patients, and as screening was not receptionists' main priority, not all patients were offered self-screening during busy periods. Patient refusal was also identified as a factor limiting uptake. Conclusion: While AF self-screening may increase screening rates, further process improvements are required to reduce impact on reception staff, and enhance the usability of the self-screening station for patients. Such improvements may increase acceptability and ongoing sustainability at a practice level. FUNDunding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Investigator initiated research grant from Bristol-Myers Squibb/Pfizer Alliance